2023
DOI: 10.2147/ppa.s397444
|View full text |Cite
|
Sign up to set email alerts
|

Collecting Patient Feedback as a Means of Monitoring Patient Experience and Hospital Service Quality – Learning from a Government-led Initiative

Abstract: Patient feedback plays a significant role in hospital service improvement. However, how to encourage patient feedback that can guide hospital service improvement is still being explored. By examining patient feedback data related to a tertiary hospital in China that was collected from the "12345" Government Service Convenience Hotline (GSCH), the paper discusses the learnings from GSCH in encouraging patient feedback and how quality improvement initiatives have effected the number and types of complaints made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Some researchers have suggested that even hospitals' supply chain management can significantly affect the service quality dimension and hospital performance [27,28]. Similarly, Han et al [29] utilized the data obtained from the government initiative of a hotline for patient feedback to measure service quality. The patients' feedback and complaints were utilized to make recommendations to the hospital to improve their service quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some researchers have suggested that even hospitals' supply chain management can significantly affect the service quality dimension and hospital performance [27,28]. Similarly, Han et al [29] utilized the data obtained from the government initiative of a hotline for patient feedback to measure service quality. The patients' feedback and complaints were utilized to make recommendations to the hospital to improve their service quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Patient involvement plays a crucial role in improving service quality to regulate and prevent harm cases, as it facilitates the identification of existing or potential medical issues, providing valuable insights for developing medical services. This concept allows for anticipating qualitative outcomes and service effectiveness while efficiently reducing patient injuries and associated medical expenses, significantly improving health status (Han et al, 2023).…”
Section: Introductionmentioning
confidence: 99%